Financial Resilience of Food and Beverage SMEs in the VUCA Era: Qualitative Study in Tuban - Fadhoilus Shofi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2026)
Purpose: This study explores how food and beverage MSMEs build financial resilience in the VUCA era through everyday financial practices, digital transactions, working capital discipline, and crisis-oriented decision making. Methodology/approach: A qualitative case study design was used. Data were collected through semi-structured interviews, observation, and document review involving selected MSME owners or managers in Tuban Regency. The data were analyzed using thematic analysis with triangulation and member checking. Results/findings: The findings show that MSME financial resilience is formed through five practices: separating business and household cash, maintaining flexible working capital, adapting prices and procurement, using fintech for transaction records, and relying on supplier-customer networks during uncertainty. Conclusions: Financial resilience in a VUCA environment is not merely determined by the size of capital, but by disciplined cash behavior, adaptive capability, digital financial literacy, and the ability to interpret market signals. Limitations: This study is limited to food and beverage MSMEs in Tuban Regency and uses qualitative interpretation based on selected informants. Contribution: The article contributes a context-based qualitative explanation of MSME financial resilience and offers practical guidance for MSME assistance programs.